THE RELATIONSHIP BETWEEN INTERPERSONAL INTELLIGENCE AND PARENTS’ ATTENTION - RETNO SETYA BUDIASNINGRUM; NURUL GISWI KOMARIAH; REDJEKI AGOESTYOWATI (CV KULTURA DIGITAL MEDIA, 2020)
Since English as a global language, it becomes a require subject that need to be studied especially for college students. English rule is different from Indonesian language therefore it is not easy for Indonesian students to study it. Language is used for communication. In learning a language, it is needed to communicate actively. It means that students need to be active in class. The students who have interpersonal intelligence mostly can communicate effectively. They like to participate in a debate or discussion. And the students who have interpersonal intelligence is tendency easy in learning a language. As well as interpersonal intelligence, parents’ attention has an important contribution in supporting their children in education, especially in learning English. Good attention will emerge discipline, motivation, responsibility of students to study. And it will bring them to get a good grade at school. The objective of this study was to determine the relationship between interpersonal intelligence and parents' attention with English speaking skills. The research was conducted at Polytechnic LP3I Bekasi, and 60 students were the respondents. The quantitative method and correlation technique were used to obtain and analyze data, which shows a positive relationship between Interpersonal Intelligence and English Speaking Skills, a positive relationship between Parents’ Attention and English - Speaking Skills, and a positive relationship between Interpersonal Intelligence, Parents’ Attention simultaneously with English Speaking Skills. Therefore, teachers are expected to motivate students to increase their communication skills by doing a lot of interaction in their community. Moreover, teachers need to make a discussion with the parents in order to make the parents giving more attention to their children.